Forging connections in the wilderness: a pilot study on Judaism and mental health in outdoor behavioural healthcare - Neuman, Michelle E. (Mental health, religion & culture, 2023)
Wilderness behavioural therapy programs take place outside of traditional office settings and focus on successful problem-solving skills instead of the underlying issues. There are few longitudinal studies on wilderness behavioural therapy and none specifically examining the connections between Judaism and mental health. Presented here is a longitudinal cohort study collecting data pre & immediately post-program, 6-months, 12-months, and 18-months post-program. The overall goal of this pilot study was to examine connections between Judaism, coping skills, and mental health. Two evidence-based Jewish spiritual measures and three evidence-based mental health measures were used. While most participants thought their connection to Judaism was important to treatment, that did not translate to using aspects of Judaism as a coping mechanism. Likewise, there were no statistically significant changes on any of the mental health measures used. One caveat: the small sample size makes for poor generalizability.